Resection of a Lumbar Intradural Extramedullary Schwannoma: 2-Dimensional Operative Video. Issue 1 (7th April 2021) - Strong, Michael J; Yee, Timothy J; Khalsa, Siri Sahib S; Saadeh, Yamaan S; Muhlestein, Whitney E; North, Robert Y; Szerlip, Nicholas J
Abstract: Schwannomas are typically benign tumors that arise from the sheaths of nerves in the peripheral nervous system. In the spine, schwannomas usually arise from spinal nerve roots and are therefore extramedullary in nature. Surgical resection-achieving a gross total resection, is the main treatment modality and is typically curative for patients with sporadic tumors. In this video, we present the case of a 38-yr-old male with worsening left leg radiculopathy, found to have a lumbar schwannoma. Preoperative imaging demonstrated that the tumor was at the level of L4-L5. A laminectomy at this level was performed with gross total resection of the tumor. The key points of the video include use of intraoperative fluoroscopy to confirm surgical level and help plan surgical exposure, use of ultrasound for intradural tumor localization, and advocating for maximum safe resection using neurostimulation. The patient tolerated the surgery well without any complications. He was discharged home with no additional therapy needed. Appropriate patient consent was obtained.